AB0535 Fatigue is associated with hs-crp in patients with systemic lupus erythematosus. (15th June 2017) - Aung, T; Sahakian, L; Skaggs, B; Grossman, J; McMahon, M
Abstract : Background: Fatigue is highly prevalent and has a negative impact on quality of life in patients with Systemic Lupus Erythematosus. 1, 2 The 9-item Fatigue Severity Scale (FSS) is one of the commonly used self-report questionnaires to measure fatigue in patients with chronic disease. 3 Although fatigue is one of the most commonly reported symptoms in SLE, previous studies have not consistently found any clear association between disease activity (as measured by the SLEDAI) 4 or with laboratory measures of disease activity. 1 Objectives: To determine whether fatigue is associated with any laboratory measures of disease activity or inflammation in patients with SLE. Methods: SLE patients and age-matched controls participating in our longitudinal "Biomarkers of Cardiovascular Disease in SLE" completed FSS questionnaires at study entry. Laboratory measures of cardiovascular risk assessment and lupus disease activity assessments were performed in plasma, including high sensitivity C-reactive protein (hs-CRP), myeloperoxidase (MPO), homocysteine, fasting lipid panels, erythrocyte sedimentation rate (ESR), C3, C4, dsDNA, and urine protein/creatinine ratio (UPCR). Results: 54 patients and 37 control individuals participated. FSS scores were higher in patients with SLE (4.79±1.63 (mean ± SD) compared to healthy subjects (3.17±1.83, P<0.001). There were no significant correlations between FSS and age, gender, or SLE disease duration. In SLE patients, there was significant correlation between FSS scores and hs-CRP (r=0.56, p=0.004), and an inverse correlation with myeloperoxidase (-0.37, p=0.045). No associations between FSS and C3, C4, dsDNA, ESR, UPCR, fasting lipid levels, or homocysteine were seen in the SLE group. No associations between FSS and laboratory measures of cardiovascular risk assessment were seen in the control group. Conclusions: Although fatigue is not correlated with traditional laboratory measures of disease activity in SLE patients, we did find significant associations between fatigue, hs-CRP, and myeloperoxidase in our cohort. Future longitudinal studies are underway to determine whether these associations also reflect the risk for progression of cardiovascular disease in patients with high fatigue. References: Krupp L B, LaRocca N G MJ et al. A study of fatigue in systemic lupus erythematosus. J Rheumatol. 1990;17(11):1450–1452. Tench CM, McCurdie I, White PD, D'Cruz DP. The prevalence and associations of fatigue in systemic lupus erythematosus. Rheumatology (Oxford). 2000;39(11):1249–1254. doi:10.1093/rheumatology/39.11.1249. Hjollund NH, Andersen JH, Bech P. Assessment of fatigue in chronic disease: a bibliographic study of fatigue measurement scales. Health Qual Life Outcomes. 2007;5:12. doi:10.1186/1477–7525–5-. Wang B, Gladman DD, Urowitz MB. Fatigue in lupus is not correlated with disease activity. J Rheumatol. 1998;25(5):892–895. Disclosure of Interest: None declared